Venture Capitalists on Boards of Mature Public Firms - Celikyurt, Ugur; Sevilir, Merih; Shivdasani, Anil (Review of Financial Studies, 2014)
Venture capitalists (VCs) often serve on the board of mature public firms long after their initial public offering (IPO), even for companies that were not VC-backed at the IPO. Board appointments of VC directors are followed by increases in research and development intensity, innovation output, and greater deal activity with other VC-backed firms. VC director appointments are associated with positive announcement returns and are followed by an improvement in operating performance. Firms experience higher announcement returns from acquisitions of VC-backed targets following the appointment of a VC director to the board. Hence, in addition to providing finance, monitoring and advice for small private firms, VCs play a significant role in mature public firms and have a broader influence in promoting innovation than has been established in the literature.